Hubungan Motivasi Kerja dengan Kinerja Pegawai di Dinas Pendidikan, Pemuda dan Olahraga Kota Pariaman - Fadilatul Istiqamah; Irsyad Irsyad; Nelfia Adi; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2026)
This study aims to examine the relationship between work motivation and employee performance at the Pariaman City Education, Youth, and Sports Office. The study employs a quantitative approach using a correlational method. The study population consists of 80 employees, with a sample of 69 respondents selected using the Stratified Proportional Random Sampling technique based on the. The research instrument consisted of a questionnaire using a Likert scale that had been tested for validity and reliability. Data analysis techniques included descriptive analysis, normality tests, linearity tests, simple correlation analysis, and t-tests to test the research hypotheses. The results of the study indicate that employee performance falls into the “good” category with an average score of 4.10 and a percentage of 82%, while work motivation falls into the “high” category with an average score of 4.08 and a percentage of 82%. The results of the Product Moment correlation analysis show a correlation coefficient of 0.623, classified as strong and positive. Furthermore, the t-test results show that t-calculated = 6.511 > t-table = 1.668 with a significance level of 0.000 < 0.05. Thus, it can be concluded that there is a significant relationship between work motivation and employee performance at the Department of Education, Youth, and Sports of Pariaman City.